Evaluation of therapeutic and prophylactic platelet transfusion practices in a neonatal intensive care unit - Korkut, Sabriye; Bozkaya, Davut; Tayman, Cuneyt (Annals of Medical Research, 2021)
None
Keywords: Thrombocytopenia; Newborn; Platelet Transfusion; Hemorrhage.